Performance Analysis of TiO2-Modified Co/MgAl2O4 Catalyst for Dry Reforming of Methane in a Fixed Bed Reactor for Syngas (H2, CO) Production - Arslan Mazhar; Asif Hussain Khoja; Abul Kalam Azad; Faisal Mushtaq; Salman Raza Naqvi; Sehar Shakir; Muhammad Hassan; Rabia Liaquat; Mustafa Anwar (Energies, 2021)
Co/TiO2–MgAl2O4 was investigated in a fixed bed reactor for the dry reforming of methane (DRM) process. Co/TiO2–MgAl2O4 was prepared by modified co-precipitation, followed by the hydrothermal method. The active metal Co was loaded via the wetness impregnation method. The prepared catalyst was characterized by XRD, SEM, TGA, and FTIR. The performance of Co/TiO2–MgAl2O4 for the DRM process was investigated in a reactor with a temperature of 750 °C, a feed ratio (CO2/CH4) of 1, a catalyst loading of 0.5 g, and a feed flow rate of 20 mL min−1. The effect of support interaction with metal and the composite were studied for catalytic activity, the composite showing significantly improved results. Moreover, among the tested Co loadings, 5 wt% Co over the TiO2–MgAl2O4 composite shows the best catalytic performance. The 5%Co/TiO2–MgAl2O4 improved the CH4 and CO2 conversion by up to 70% and 80%, respectively, while the selectivity of H2 and CO improved to 43% and 46.5%, respectively. The achieved H2/CO ratio of 0.9 was due to the excess amount of CO produced because of the higher conversion rate of CO2 and the surface carbon reaction with oxygen species. Furthermore, in a time on stream (TOS) test, the catalyst exhibited 75 h of stability with significant catalytic activity. Catalyst potential lies in catalyst stability and performance results, thus encouraging the further investigation and use of the catalyst for the long-run DRM process.